“Au tans le roi Artu”: The Heroic “Languages” of the “Suite vulgate” in “Merlin” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
In the prose romance Suite Vulgate du Merlin (known as Les premiers faiz le roy Artu by the Bonn manuscript), the story is conceived as an introduction to the deeds of king Arthur and his main knights, staged as young protagonists of adventurous enfances laying the foundations of the Arthurian kingdom. At the center of the analysis will therefore be a double construction process: the construction of individual characters, seen in their beginning; the building of a heroic age that imposes heroic models and codes, a “grammar” for the Arthurian mythology.
Keywords: hero; enfances; Arthur; medieval romance; mythology